Clinical Characteristics and Outcomes in People Living With Human Immunodeficiency Virus Hospitalized for Coronavirus Disease 2019. (30th May 2020) - Shalev, Noga; Scherer, Matthew; LaSota, Elijah D; Antoniou, Pantelis; Yin, Michael T; Zucker, Jason; Sobieszczyk, Magdalena E
Abstract: We describe the characteristics of 31 people living with human immunodeficiency virus hospitalized for severe acute respiratory syndrome coronavirus 2 infection. All patients were on antiretroviral therapy and virologically suppressed at the time of admission. Clinical course and outcomes were similar to those reported in other hospitalized cohorts.